A case report of an unusual left atrial mass. Issue 1 (28th December 2020) - Udemgba, Chinelo; Missov, Emil; Percy, Robert; Sattiraju, Srinivasan
Abstract: Background: Cardiac foreign bodies (FBs) are rare findings that may present as cardiac masses initially. Here, we present an exceptional and rare case of a hypodermic needle FB that transmigrated to the left atrium and presented as a left atrial mass. Case summary: A 28-year-old woman with multiple psychiatric disorders including intentional FB ingestion and self-inflicting injuries presented to the emergency room with abdominal pain, nausea, vomiting, diarrhoea, and chest pain that radiated to the left arm and face for 2 weeks. An echocardiogram was performed revealing a left atrial mass concerning for myxoma. During the surgical removal of the mass, a hypodermic needle was found attached to the roof of the left atrium surrounded by thrombotic and fibrotic tissue, which was confirmed by pathology. Discussion: Cardiac FBs are caused generally by penetrating wounds from direct trauma. Fewer cases have been reported regarding cardiac FB caused by ingestion from migration of the object to the heart. Signs and symptoms for cardiac FB may mimic those of cardiac masses. Cardiac FBs often require surgical intervention to avoid complications.